2015
DOI: 10.33844/ijol.2015.60224
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Model of Organizational Agility: A Case Study of Ardabil Gas Company

Abstract: Organizational agility means the ability of every organization in sensation, perception, and prediction of available changes in the business environment. The importance of organizational agility in a competitive environment is nowadays widely recognized and accepted. The aim of this research was to design a unified theoretical model of organizational agility for Ardabil Gas Company based upon the theoretical principles of organizational agility proposed by Goldman (1995). Independent variables including organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Agile individuals are people who have the abilities, knowledge, and skills to proactively seek opportunities, and they are able to adapt quickly to new situations (Doeze Jager-van Vliet, 2017; Razmi & Ghasemi, 2015). They are further defined as individuals who are equipped with the skills to anticipate, implement, and exploit changes and take advantage of them (Braun et al, 2017;Chonko & Jones, 2005).…”
Section: Agile Individualsmentioning
confidence: 99%
“…Agile individuals are people who have the abilities, knowledge, and skills to proactively seek opportunities, and they are able to adapt quickly to new situations (Doeze Jager-van Vliet, 2017; Razmi & Ghasemi, 2015). They are further defined as individuals who are equipped with the skills to anticipate, implement, and exploit changes and take advantage of them (Braun et al, 2017;Chonko & Jones, 2005).…”
Section: Agile Individualsmentioning
confidence: 99%
“…Due to the rapid changes and intense competition, researchers are trying to produce strategies that can ensure the sustainability of the organizations and be effective and suitable for them (Bakan et al, 2017). Based on this idea, it is emphasized that in today's modern environment, every agile organization must have the power to produce different short-lived products at the same time, redesign their daily products, change the production method, and react efficiently to changes (Razmi & Mohammad Ghasemi, 2015). For this, organizations need to have a high speed in decision making, flexibility and adaptability, and at the same time have a skilled, creative and responsible workforce who can work well in a team.…”
Section: R M B Rmentioning
confidence: 99%
“…The twenty-first century brought rapid and dramatic changes in the manufacturing and service sectors of organizations (Razmi & Mohammad Ghasemi, 2015). In such a case, the globalization process is undoubtedly one of the most important factors that deeply affect the business world by increasing the level of competition in most industries (Lawler & Worley, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An agile organization is able to sense the changes, predict the dimension and nature of change and perceive the change in its true sense. Razmi & Ghasemi (2015) observed that trust plays a vital role in mediating between organizational commitment and technological capabilities. Sharifi & Zhang (2001) reported the importance of agility in the context of achieving sustainability in business while operating in a turbulent environment.…”
Section: Supply Chain Analytics (Sca) and Its Impact On Supply Chain mentioning
confidence: 99%